Interpersonal metadiscourse : changing patterns in linguistics book reviews - Lee, Bryan Yong Huan; Ang, Leng Hong (Penerbit Universiti Kebangsaan Malaysia, 2024)
This corpus-based study examines metadiscourse in linguistics book reviews across three key years: 2002, 2012, and 2022. Its aim is to trace the evolution and usage patterns of metadiscourse markers over this twenty-year span. Using Hyland’s (2005) Interpersonal model, the research delves into both interactive and interactional metadiscourse. The study analyses various types of interactive metadiscourse markers, including transitions, code glosses, endophorics, frame markers, and evidentials. It also examines interactional metadiscourse, focusing on elements like self-mentions, attitude markers, hedges, boosters, and engagement markers. The findings show a notable consistency in the use of these markers across the studied years. Specifically, transitions are the most frequently used in interactive metadiscourse, followed by frame markers and others. In interactional metadiscourse, hedges are most prevalent, followed by engagement markers and others. By observing metadiscourse changes over two decades, the study offers insights into the evolving academic conventions and adaptations in writing practices in response to changing demands in scholarly communication. The results reveal a slight increase in the use of interactive metadiscourse markers and a small decline in interactional markers from 2002 to 2022. This trend highlights the dynamic nature of academic writing and emphasises the increasing importance of metadiscourse in structuring academic discourse and engaging readers. These findings provide insights for linguistics researchers and the broader academic community, underscoring the critical role of metadiscourse in effective scholarly communication.